Pengaruh Penggunaan AI dan Dukungan Manajemen Terhadap Produktivitas Kerja dengan Kinerja Karyawan Sebagai Variabel Mediasi - Roza Aulina Hidayat; Jati Waskito (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of Artificial Intelligence (AI) usage and managerial support on work productivity, with employee performance as a mediating variable, focusing on administrative staff at Universitas Muhammadiyah Surakarta. A descriptive quantitative approach was employed, using purposive sampling of 100 respondents from a population of 300 employees. Data were collected via questionnaires and analyzed using multiple linear regression and the Sobel test to assess mediation effects. The results indicate that AI usage has a positive and significant effect on work productivity but is not significant in improving employee performance. In contrast, managerial support has a significant effect on both productivity and performance. However, employee performance does not significantly mediate the relationship between AI usage and managerial support on productivity. The study concludes that managerial support plays a crucial role in enhancing both productivity and performance, while AI contributes more directly to work efficiency. These findings offer valuable implications for HR policy development and the implementation of technology in the workplace.